If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 3(2s + -5) Reorder the terms: 9 = 3(-5 + 2s) 9 = (-5 * 3 + 2s * 3) 9 = (-15 + 6s) Solving 9 = -15 + 6s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-6s' to each side of the equation. 9 + -6s = -15 + 6s + -6s Combine like terms: 6s + -6s = 0 9 + -6s = -15 + 0 9 + -6s = -15 Add '-9' to each side of the equation. 9 + -9 + -6s = -15 + -9 Combine like terms: 9 + -9 = 0 0 + -6s = -15 + -9 -6s = -15 + -9 Combine like terms: -15 + -9 = -24 -6s = -24 Divide each side by '-6'. s = 4 Simplifying s = 4
| 2(5d-5)=-40 | | 4(3i+3)=24 | | 2(4v-2)=20 | | -18=3(2g-2) | | 2*3*150= | | 95=11-14y | | 48=9+3u | | 4=6u-2 | | 4+11k=103 | | 30*32*9= | | 6-3u=18 | | 12*3.14= | | -16=3z+5 | | 5*3.14= | | 11*3.14= | | -20=7-3q | | 9*3.14= | | 10x+4x=126 | | 9n-3(2n-1)=12 | | SV+2=52 | | 2k+1=19 | | 7*3.14= | | 4z+4=32 | | 6*3.14= | | 4x-2(3y-5)= | | 450*5.25*2.5= | | 5-3*K=19 | | 3x=44-9x | | 6x^2+24=0 | | 15x=27+12x | | 9+11x=29+9x | | 17x-3=16x+9 |